(3OQGSI JLGQH OhdjIs - (3aJjMI(B, (3HhYHGfIs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jJWQb gPG GdcJGH Gdi eGgjI GdeMGSHI GdYehejI, eYGjjQ eMGSHjI OhdjI ddbWGY GdYGe (BIPSAS(3, eLdS eYGjjQ GdeMGSHjI GdOhdjI ddbWGY GdYGe, YQV eYGjjQ GdeMGSHjI GdOhdjI ddbWGY GdYGe, JLGQH Ohd YQHjI hCLfHjI aj GUdGM GdeMGSHI GdYehejI hab CSGS GdGSJMbGb hGdeYGjjQ GdOhdjI(B. s
(3HHdjhZQGajG(B: (3U U(B.189-198s
Keywords: (3GdeMGSHI GdOhdjIs; (3GdeMGSHI GdYehejIs; (3eYGjjQ GdeMGSHIs